Gross domestic product and geographic area as social determinants of child stunting and severe stunting in Indonesia: A multilevel analysis - Siswati, Tri; Waris, Lukman; Paramashanti, Bunga Astria; Kusnanto, Hari; Susilo, Joko (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2022)
Background: In Indonesia, socioeconomic disparities in childhood stunting is vast.Objectives: This study aimed to analyze the social determinants of stunting and severe stunting children in Indonesia.Methods: We analyzed data from cross-sectional surveys of Indonesia’s National Basic Health Research in 2013, the Central Bureau of Statistics, and the Ministry of Finance. Our samples were 3953 children aged 6-23 months and 10215 children aged 24-59 months. Dependent variables were the prevalence of child stunting and severe stunting. Independent variables covered factors at the social level while controlling structural and biological level-factors. Data were analyzed using multilevel analysis using generalized linear mixed models (GLMM).Results: Gross domestic product was associated with the reduced risk of stunting among children aged 6-23 months (ARRR= 0.99; 95%CI: 0.98-1.00) and 24-59 months (ARRR= 0.99; 95%CI: 0.97-0.99) as well as with the decreased risk of severe stunting among 6-23 months (ARRR= 0.99; 95%CI: 0.98-1.00) and 24-59 months (ARRR= 0.99; 95%CI: 0.97-0.99) old children. Tax ratio was a significant factor only for the severe stunting among 24-59 months old children (ARRR= 0.98; 95%CI: 0.96-0.99). There was also a geographical difference related to stunting and severe stunting.Conclusions: Equitable economic growth is an essential factor to improve the health and welfare of stunting and severe stunting children across the geographical setting in Indonesia.